2021
DOI: 10.1186/s12889-021-10960-0
|View full text |Cite
|
Sign up to set email alerts
|

Home food procurement impacts food security and diet quality during COVID-19

Abstract: Background Home food procurement (HFP) (i.e. gardening, fishing, foraging, hunting, backyard livestock and canning) have historically been important ways that people obtain food. Recently, some HFP activities have grown (e.g. gardening), while other activities (e.g. hunting) have become less common in the United States. Anecdotally, COVID-19 has sparked an increase in HFP evidenced by increased hunting licenses and shortages in seeds and canning supplies. HFP may have positive benefits for food… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 57 publications
5
66
3
1
Order By: Relevance
“…Conversely, some respondents in our study reported eating more fruits and vegetables, aligning with early evidence from Germany, Denmark (quota-based sample) ( Janssen et al, 2021 ), Australia (convenience sample) ( Eat Well Tasmania, 2020 ), Italy (convenience sample) ( Di Renzo et al, 2020b ), and Spain (convenience sample) ( Rodríguez-Pérez et al, 2020 ), suggesting that the relatively consistent supply of fresh produce in some countries, combined with strong social safety nets, may result in increased consumption by consumers motivated to adopt healthier habits. Interestingly, a state wide representative study in the USA demonstrated that some food insecure households actually increased fruit and vegetable intake during the pandemic due to utilisation of food aid ( Bertmann et al, 2021 ) and home food self-sufficiency (e.g., gardening, fishing, foraging, and hunting) ( Niles et al, 2021b ). Disparate changes in dietary intake in more developed countries ( Di Renzo et al, 2020b ; Giacalone et al, 2020 ; Janssen et al, 2021 ; León and Arguello, 2021 ; UNICEF, 2020 ) also implies that heightened stress, emotional eating and variations in food literacy skills may underscore contrasting changes in eating behaviors ( Bemanian et al, 2021 ; Bhutani and Cooper, 2020 ; Di Renzo et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, some respondents in our study reported eating more fruits and vegetables, aligning with early evidence from Germany, Denmark (quota-based sample) ( Janssen et al, 2021 ), Australia (convenience sample) ( Eat Well Tasmania, 2020 ), Italy (convenience sample) ( Di Renzo et al, 2020b ), and Spain (convenience sample) ( Rodríguez-Pérez et al, 2020 ), suggesting that the relatively consistent supply of fresh produce in some countries, combined with strong social safety nets, may result in increased consumption by consumers motivated to adopt healthier habits. Interestingly, a state wide representative study in the USA demonstrated that some food insecure households actually increased fruit and vegetable intake during the pandemic due to utilisation of food aid ( Bertmann et al, 2021 ) and home food self-sufficiency (e.g., gardening, fishing, foraging, and hunting) ( Niles et al, 2021b ). Disparate changes in dietary intake in more developed countries ( Di Renzo et al, 2020b ; Giacalone et al, 2020 ; Janssen et al, 2021 ; León and Arguello, 2021 ; UNICEF, 2020 ) also implies that heightened stress, emotional eating and variations in food literacy skills may underscore contrasting changes in eating behaviors ( Bemanian et al, 2021 ; Bhutani and Cooper, 2020 ; Di Renzo et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a range of literature regarding changes in food supply ( Chenarides et al, 2020 ; Priyadarshini and Abhilash, 2021 ; Tesfaye et al, 2020 ), food security ( Ceballos et al, 2021 ; Egger et al, 2021 ; Laborde et al, 2021 ; Niles et al, 2020b ; Sharma et al, 2020 ), and food consumption ( Enriquez-Martinez et al, 2021 ; Janssen et al, 2021 ; León and Arguello, 2021 ; Maredia, 2020 ; Niles et al, 2021b ) during Covid-19, very few studies have assessed the impact of the pandemic on consumer food behaviors through a food environment lens. To our knowledge, there is only one multi-country food environment study that was conducted by the Food and Agricultural Organization (FAO) of the United Nations (UN) ( FAO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lades et al [60] reported gardening to be one of the most effective activities for mitigating the negative effects of social isolation due to COVID-19 on people's emotional well-being. As shown by Niles et al [61] and Montefrio [57], home food procurement from gardening and foraging had spread during the pandemic, with positive benefits for food security and diet quality. It is known that growing one's own produce is linked to an increase in fruit and vegetable intake.…”
Section: The Impact Of Covid-19 On Horticulture As a Hobby And On Ordinary Peoplementioning
confidence: 99%
“…Since then, the global COVID-19 pandemic has impacted aspects of food acquisition and created economic challenges. There is some evidence that this has resulted in increased gardening and home food production [52]. More recent data collection on the measures analyzed here would further understand the relationship between gardening and vegetable acquisition in the current context.…”
Section: Discussionmentioning
confidence: 87%